Emancipate social media platform in invigorating green technology initiative for library sustainable communities - Mazlan, Mazwani Ayu; Mohd Shoid, Mohd Shamsul; Baharuddin, Mohammad Fazli; Tengku Izhar, Tengku Adil (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
When it comes to implementing green innovation strategies, libraries are cautious to do so unless those techniques offer immediate cost benefits. This is because of the perceived risk involved in making investments for the short term with the goal of achieving long-term advantages, which is in contrast to the emphasis placed on short-term quarterly returns in corporate settings. The goal of fully implementing environmentally friendly methods across the entirety of the product life cycle is a valuable endeavour because of the potential for growth that it gives to people who are looking for excitement. The absence of a comprehensive framework that incorporates social media in order to promote the significance of environmentally friendly technology in libraries is the reason for this situation. The purpose of this research is to provide a structural framework that makes use of social media in order to improve the green technology library project. The framework that has been developed will raise the people in the library community's knowledge of the importance of environmental sustainability. The aspects of green library for environment sustainability were obtained from the reviewing articles indicating resources, environmental, material, educational and management as well as factors to implement of the green library; Energy, education and management. This study will establish green library practices to benefit the environment, whether explicitly stated or not, to improve human well-being. Humans are clearly harming the ecosystem. Libraries, as public institutions that improve society, should protect the environment. This research can alert the community to our situation and empower them to change. Libraries realise that their eco-friendly building can educate the public. Libraries are centered on improving humanity; hence sustainability is important. Green libraries often provide environmental education programmes to demonstrate how their architecture and operations reflect these ideas. The significance of this cannot be overstated because society is an essential element of the concept of sustainability. It is important to ensure that library patrons have access to materials while also preserving their health in an atmosphere that is sustainable. There were a variety of recommendations regarding the implementation of a green library towards the environment world. One of these recommendations was to implement a wide expectation building development practices and procedures.